The Effect of a Strength Training Session on Alpha Phytoprotein, Gamma Glutamyl Transferase and Alkaline Phosphatase in People with Regular Training and Forced Non-Training Due to Covid-19 - mohammad amini; aghgali ghasemnian; hasan gharehkhani; reza kheyrandish (Armaghane Danesh Bimonthly Journal, 2023)
Mohammadyari S, Hadi H, Saberi Y. Investigation of physiological effects (immune system) of Exercise in COVID-19 epidemic; By providing a training protocol (Systematic review). Journal of Applied Health Studies in Sport Physiology 2021; 8(1): 88-101. 5.Gaeini A, Ghasemnian A, Dehkordi K, Kazemi A, Fallahi A. The comparison of the effect a single acute exercise on plasma, CRP, TNFα and IL-6 levels in immature obese and normal-weight boys. Journal of Mazandaran University of Medical Sciences 2011; 21(83): 74-8. 6.kemefuna F, Meludu S, Dioka C, Onah C, Okwara J, Nwankwo M, et al. Pattern of some liver enzymes and cardiovascular changes during a trademill exercise. IOSR Journal of Pharmacy 2014; 4: 7-24. 7.Pettersson J, Hindorf U, Persson P, Bengtsson T, Malmqvist U, Werkström V, et al. Muscular exercise can cause highly pathological liver function tests in healthy men. British Journal of Clinical Pharmacology 2008; 65(2): 253-9. 8.Amireault S, Baier JM, Spencer JR. Physical activity preferences among older adults: A systematic review. Journal of Aging and Pysical Activity 2018; 27(1): 128-39. 9.Schidt FV, Ostapowicz G, Murray N, Satyanarana R, Zaman A, Munoz S, et al. Alpha-fetoprotein and prognosis in acute liver failure. Liver Transplantation 2006; 12(12): 1776-81. 10.Zahedpasha Y, Tamaddoni A, Ahmadpour-kacho M, Pourmoghtader S. Serum αFP level in cord blood of full term neonates born in babol city. Journal of Babol University of Medical Sciences 2019; 21(1): 135-9. 11.Otağ A, Hazar M, Otağ İ, Beyleroğlu M. Effect of increasing maximal aerobic exercise on serum gonadal hormones and alpha-fetoprotein in the luteal phase of professional female soccer players.           J Phys Ther Sci 2016; 28(3): 807-10. 12.Schidt FV, Ostapowicz G, Murray N, Satyanarana R, Zaman A, Munoz S, et al. Alpha-fetoprotein and prognosis in acute liver failure. Liver Transplantation 2006; 12(12): 1776-81. 13.Beydilli H, Yilmaz N, Cetin ES, Topal Y, Celik OI, Sahin C, et al. Evaluation of the protective effect of silibinin against diazinon induced hepatotoxicity and free-radical damage in rat liver. Iran Red Crescent Med J 2015; 17(4): e25310. 14.Amireault S, Baier JM, Spencer JR. Physical activity preferences among older adults: A systematic review. Journal of aging and physical activity. 2019 Feb 1;27(1):128-39 15.Esmaelzadeh Toloee M, Faramarzi M, Noroozian P. effect of aerobic training with ginger supplementation on some liver enzymes (AST, ALT, GGT) and resistance to insulin in obese women with type 2 diabetes. Medical Journal of Mashhad University of Medical Sciences 2017; 60(4): 636-47. 16.Ayça B, Agopyan A, Sener A, Oba R, Pastirmaci G. Evaluation of gamma-glutamyl transferase changing in urine related to the training load in the rhythmic gymnasts’ competitors aged 7-10. Biology of Sport 2008; 25(3): 233-44. 17. Samani Jahormi EL, Zulqadri Jahormi S. Effect of alkaline phosphatase on the enzymes and proteins of liver tissue of rat by enzyme inhibition. Journal of Animal Biology 2015; 7(4): 177-88. 18.Marzban A, Seyedalipour B, Mianabadi M, Taravati A. Investigation of the Enzyme activities of alkaline phosphatase, lactate dehydrogenase, transaminase and histopathological changes of liver after exposure to nio and nio nanoparticles in rats. The Journal of Shahid Sadoughi University of Medical Sciences 2017; 25(5): 381-95. 19.Hosseini Kakhk A, Khalegh Zadeh H, Nematy M, Hamedi Nia M. The effect of combined aerobic-resistance training on lipid profile and liver enzymes in patients with non-alcoholic fatty liver under nutrition diet. Sport Physiology 2015; 7(27): 65-84. 20.Galedari M, Kaki A. The effect of 12 weeks high intensity interval training and resistance training on liver fat, liver enzymes and insulin resistance in men with nonalcoholic fatty liver. Jundishapur Scientific Medical Journal 2017; 16(5): 493-503. 21.Shamsoddini A, Sobhani V, Chehreh MEG, Alavian SM, Zaree A. Effect of aerobic and resistance exercise training on liver enzymes and hepatic fat in Iranian men with nonalcoholic fatty liver disease. Hepatitis Monthly 2015;15(10): 431-439. 22.Ghanbari Niaki A, Tayebi S-m, Ghorban Alizade Ghaziani F, Hakimi J. The effect of a single-circuit weight-training session on lipid profiles and serum lipoprotein changes in students of physical education. Journal of Applied Exercise Physiology 2006; 2(4): 35-44. 33.Asouri M. Acute Effects of jujube ziziphus solution feeding before a single session of circuit resistance exercise on apoptosis of human neutrophil. Journal of Applied Exercise Physiology 2017; 13(25): 97-114. 24.Jürimäe T, Karelson K, Smirnova T, Viru A. The effect of a single-circuit weight-training session on the blood biochemistry of untrained university students. European Journal of Applied Physiology and Occupational Physiology 1990; 61(5): 344-8. 25.Mihalik JP, Libby JJ, Battaglini CL, McMurray RG. Comparing short-term complex and compound training programs on vertical jump height and power output. The Journal of Strength & Conditioning Research 2008; 22(1): 47-53. 26. Ko IG, Park EM, Choi HJ, Yoo J, Lee JK, Jee YS. Proper exercise decreases plasma carcinoembryonic antigen levels with the improvement of body condition in elderly women. The Tohoku Journal of Experimental Medicine. 2014;233(1):17-23. 27.Mousavian AS, Darvakh H. Effect of combined aerobic exercise on serum level of liver gamma glutamil transferase and glycemic index of middle-aged diabetic women. The Iranian Journal of Obstetrics, Gynecology and Infertility 2016; 19(1): 9-19. 28.Moradi Kelardeh B, Azarbayjani MA, Peeri M, Matin Homaee H. Effects of nonlinear resistance training on liver biochemical marker levels in postmenopausal women with nonalcoholic fatty liver disease. The Scientific Journal of Rehabilitation Medicine 2016; 5(4): 136-45. 29.Nazarieh E, Ghaedi H, Taghipour- Asrami A. Effect of 8 weeks resistance training with zataria multiflora supplementation on liver enzymes, hepatic steatosis index in men with non-alcoholic fatty liver. Journal of Applied Exercise Physiology 2020; 16(31): 115-26. 30.Johnson NA, Sachinwalla T, Walton DW, Smith K, Armstrong A, Thompson MW, et al. Aerobic exercise training reduces hepatic and visceral lipids in obese individuals without weight loss. Hepatology 2009; 50(4): 1105-12. 31.Naghizadeh H, Azizbeigi K. Effect of 12 weeks of progressive resistance training on the serum levels of liver enzymes Aspartate Aminotransferase, Alanine aminotransferase, alkaline phosphatase in sedentary obese men. Metabolism and Exercise 2019; 9(2): 85-162. 32.Rowell LB, Blackmon JR, Bruce RA. Indocyanine green clearance and estimated hepatic blood flow during mild to maximal exercise in upright man. The Journal of Clinical Investigation 1964; 43(8): 1677-90. 33.Fathi R, Nasiri K, Akbari A, Ahmadi-KaniGolzar F, Farajtabar Z. Exercise protects against ethanol-induced damage in rat heart and liver through the inhibition of apoptosis and activation of Nrf2/Keap-1/HO-1 pathway. Life Sciences 2020; 256: 117958. 34.Aoi W, Naito Y, Hang LP, Uchiyama K, Akagiri S, Mizushima K, et al. Regular exercise prevents high-sucrose diet-induced fatty liver via improvement of hepatic lipid metabolism. Biochemical and Biophysical Research Communications 2011; 413(2): 330-5. 35.Strasser B, Schobersberger W. Evidence for resistance training as a treatment therapy in obesity. Journal of Obesity 2011; Volume 2011, 9 pages. doi:10.1155/2011/482564 36.Otağ A, Hazar M, Otağ İ, Beyleroğlu M. Effect of increasing maximal aerobic exercise on serum gonadal hormones and alpha-fetoprotein in the luteal phase of professional female soccer players. Journal of Physical Therapy Science 2016; 28(3): 807-10.